2013
DOI: 10.1111/febs.12204
|View full text |Cite
|
Sign up to set email alerts
|

Protein–fatty acid complexes: biochemistry, biophysics and function

Abstract: Thirteen years ago, α‐lactalbumin (α‐LA) was first reported to form a complex with oleic acid (OA). This complex, called HAMLET (human α‐lactalbumin made lethal to tumour cells), was found to be cytotoxic to cancer cells. In HAMLET, α‐LA assumes a partially unfolded conformation and can bind OA in various stoichiometries. Subsequently, different groups have been able to prepare HAMLET‐like cytotoxic complexes in different ways, which all involve the destabilization of α‐LA, and a number of different proteins h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 115 publications
(295 reference statements)
3
42
0
1
Order By: Relevance
“…1-3 together, it is possible to say that α-La insertion into membrane leads to changes in liposome morphology, being this dependent on the L/P ratio and in line with the literature [13,15,28,45,52,73,74,84,85]. Importantly, structural perturbations of the membrane and lipid reorganization are also dependent on the concentration of the protein partitioned into or adsorbed to the membrane surface [85,86]. Indeed, for globular proteins and below a certain concentration, adsorption to lipid bilayer is suggested to happen along with small membrane reorganization [85].…”
Section: Flim Reveals Differences In the Interaction Between α-La Andsupporting
confidence: 70%
“…1-3 together, it is possible to say that α-La insertion into membrane leads to changes in liposome morphology, being this dependent on the L/P ratio and in line with the literature [13,15,28,45,52,73,74,84,85]. Importantly, structural perturbations of the membrane and lipid reorganization are also dependent on the concentration of the protein partitioned into or adsorbed to the membrane surface [85,86]. Indeed, for globular proteins and below a certain concentration, adsorption to lipid bilayer is suggested to happen along with small membrane reorganization [85].…”
Section: Flim Reveals Differences In the Interaction Between α-La Andsupporting
confidence: 70%
“…This is consistent with our finding that HAMLET was more active against M. tuberculosis with increasing oleic acid content. The function of the protein component, e.g., ␣-lactalbumin in HAMLET, is believed to increase the solubility of the fatty acid by shielding it from water (61,62,66). Our observation that HAMLET is approximately 10-fold more efficient in killing M. tuberculosis than the same molar amount of oleic acid, while ␣-lactalbumin had no significant effect on the viability of M. tuberculosis in vitro (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Elovl6 -/mice than in wild-type mice, presumably owing to its efficient conversion to 217 transmembrane potential, activation of caspase-3, and the production of reactive oxygen 241 species (Brinkmann et al 2013;Fontana et al 2013). In the current study, we found that, 242 beginning soon after its addition to the cultures, CVA was severely cytotoxic to HaCaT 243 cells, mouse peritoneal macrophages, and primary keratinocytes; CVA can thus be 244 added to the list of possible lipotoxins.…”
Section: Elovl6 -/Mice Show Increased Keratinocyte Death After Mechanmentioning
confidence: 99%